2022
DOI: 10.1155/2022/8153791
|View full text |Cite|
|
Sign up to set email alerts
|

Analysing Hate Speech against Migrants and Women through Tweets Using Ensembled Deep Learning Model

Abstract: Twitter’s popularity has exploded in the previous few years, making it one of the most widely used social media sites. As a result of this development, the strategies described in this study are now more beneficial. Additionally, there has been an increase in the number of people who express their views in demeaning ways to others. As a result, hate speech has piqued interest in the subject of sentiment analysis, which has developed various algorithms for detecting emotions in social networks using intuitive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Performing exhaustive analysis for various ML classifiers, Asif et al 24 achieved accuracy of >$$ > $$80% for multiple classifiers such as SVM, random forest ensemble (RFE), and MLP across various datasets, all having text in a different language. However, they could get >$$ > $$90% accuracy only in DL recurrent models, an ensemble of baseline and boosting‐ensemble ML classifiers with word embeddings, and a CNN—MLP—language‐transformer combination model 25 .…”
Section: Related Workmentioning
confidence: 99%
“…Performing exhaustive analysis for various ML classifiers, Asif et al 24 achieved accuracy of >$$ > $$80% for multiple classifiers such as SVM, random forest ensemble (RFE), and MLP across various datasets, all having text in a different language. However, they could get >$$ > $$90% accuracy only in DL recurrent models, an ensemble of baseline and boosting‐ensemble ML classifiers with word embeddings, and a CNN—MLP—language‐transformer combination model 25 .…”
Section: Related Workmentioning
confidence: 99%
“…To build the dataset, they relied on expert annotation using a combination of techniques to collect data from Twitter, including hateful keywords related to Spanish and Latin American contexts. Plaza-Del-Arco et al and Hasan et al used HatEval to train and compare several machine learning models to detect HS against immigrants [22,23]. Arcila-Calderón et al manually created an ad hoc dataset to train deep and shallow learning models to detect anti-immigrant speech in European Spanish [15].…”
Section: Related Workmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%